Foreign Language Anxiety and Student Interpreters’ Learning Outcomes: Implications for the Theory and Measurement of Interpretation Learning Anxiety - Chiang, Yung-Nan (Meta, 2010)
Although anxiety has been documented as an important variable in both interpretation performance and second language acquisition, there has been virtually no research on the interconnections between the anxiety reactions induced by these two cross-linguistic / cultural endeavors. A review of the literature on anxiety and interpretation performance finds that most of the existing studies have treated the anxiety induced by interpretation as a transfer of other general types of anxieties, such as trait anxiety, without considering the probable role of second language anxiety in interpretation performance. In order to determine the role of foreign language anxiety in 213 Chinese-English interpretation students’ learning outcomes, which were indexed by the participants’ mid-term exam scores and semester grades, this study employed Spielberger’s (1983) Trait Anxiety Inventory to measure the students’ trait anxiety, while utilizing Horwitz, Horwitz et al.’s (1986) Foreign Language Classroom Anxiety Scale (FLCAS) to measure the participants’ foreign language anxiety. Results of correlation analyses showed that a) trait anxiety was not related to either mid-term exam scores or semester grades, b) foreign language anxiety was significantly and negatively associated with both outcome measures, c) after controlling for the effect of trait anxiety, the relationship between foreign language anxiety and interpretation learning outcomes remained significant, and d) a vast majority of the FLCAS items had significant and negative associations with both outcome measures. Implications for developing a theory of and a measurement instrument for interpretation learning anxiety are suggested.